(untitled) (Вісник: Міжнародні відносини, 2021)
The article analyzes the challenges and priorities of the Council of Europe’s information policy in the field of information security and freedom of expression. The analysis is based on the latest research of leading international researchers, specialized bodies of the Council of Europe and universities. The main challenges in the information policy of the Council of Europe are related to information security in the era of global information technology innovations. The basis of all activities of the Council of Europe is a human rights act – the European Convention for the Protection of Human Rights and Fundamental Freedoms (ECHR), or in short – the European Convention on Human Rights. This regional instrument is a binding act for the regulation of information policy, as well as for the information security of the member states of the Council of Europe, which thereby undertook to protect the rights established therein, including the right to freedom of expression. It should be emphasized that the European Convention on Human Rights is a legally binding treaty, which in most countries of the continent has an almost constitutional status.